IDENTIFIKASI KEMAMPUAN BERHITUNG PADA MATERI PENJUMLAHAN BERDASARKAN COUNTING ON DI SD MUHAMMADIYAH 2 TARAKAN - Eka Widyawati; Hariaty Hamid; Setia Widia Rahayu (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2019)
This study aims to identify the level of students' mathematical arithmetic skills in solving problems in the summing material based on counting on in class II of SD Negeri 018 Tarakan. The method used is a quantitative approach to the type of descriptive explanation. The results of the study were obtained from the students' numeracy ability test results based on the mathematics numeracy ability category of students in the high and medium categories. The problems used to identify the ability to count scheme are three problems, namely problems related to counting on, counting all, then counting on and counting all. The results of students' math skills based on the counting on scheme were obtained through interviews with 25 research subjects. Problem 1 was solved by students with a counting scheme of 10 students (40%), Problem 2 was solved by students with a counting scheme of 1 student (4%). Problem 3 is solved by students with a counting on scheme of 2 students (8%).